Phytochemical and metabolic profiling of the different Podocarpus species in Egypt: Potential antimicrobial and antiproliferative activities - Nabil Z. Mohamed; Lamis Shaaban; Samia Safan; Ashraf S.A. El-Sayed (Heliyon, 2023)
Podocarpus is the most dominant genus of Podocarpaceae, with higher taxonomical proximity to the Taxaceae, having numerous pharmaceutical applications, however, scarce studies dealing with the physiological and metabolic criteria of Podocarpus in Egypt were reported. Thus, the objective of this work was to assess the physiological and metabolical patterns of the different species of Podocarpus; P. gracilior, P. elongates, P. macrophyllus and P. neriifolius. The highest terpenoids contents were reported in P. neriifolius, followed by P. elongatus, and P. macrophyllus. P. gracilior had the highest antioxidants amount, followed by P. macrophyllus, P. neriifolius and P. elongatus. From the GC/MS metabolic profiling, caryophyllene, β-cadinene, β-cuvebene, vitispirane, β-cadinene and amorphene were the most dominant metabolites in P. gracilior. β-Caryophyllene was the common in P. gracilior, P. elongatus, P. macrophyllus and P. neriifolius with an obvious fluctuation. The plant methanolic extracts have an obvious activity against the multidrug resistant bacteria; E. coli, P. aeruginosa, S. pyogenes and S. aureus, and fungi; A. fumigatus, A. flavus, A. niger and C. albicans in a concentration-dependent manner. The highest Taxol yield was assessed in the extracts of P. elongatus (16.4 μg/gdw), followed by P. macrophyllus, and P. neriifolius. The chemical identity of Taxol derived from P. elongatus was resolved by LC/MS, with molecular mass 854.6 m/z, and similar structural fragmentation pattern of the authentic one. The highest antitumor activity of P. elongatus extracted Taxol was assessed towards HCT-116 (30.2 μg/ml), HepG-2 (53.7 μg/ml) and MCF-7 (71.8 μg/ml). The ITS sequence of P. elongatus “as potent Taxol producer” was deposited on Genbank with accession #ON540734.1, that is the first record of Podocarpus species on Genbank.